2003
DOI: 10.1177/0047287502239034
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the Demand for International Business Tourism

Abstract: Previous research in the area of tourism demand modeling and forecasting has paid little attention to business tourism. This study provides the most comprehensive comparison to date of the accuracy of modern forecasting methods in the context of international business tourism demand forecasting. Seven forecasting models are examined, including the error correction model and various structural time-series and autoregressive integrated moving average (ARIMA) models. The empirical results show that relative forec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
123
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(139 citation statements)
references
References 19 publications
11
123
0
3
Order By: Relevance
“…Cycles do not feature in any markets over the observed sample period. This is consistent with most of the tourism demand literature using CSMs, such as the studies of González and Moral (1995) and Kulendran and Witt (2003). It indicates that the key economic determinants included have successfully explained the variation in the tourism demand variable, and therefore it is not necessary to include an additional cyclical component (Moosa, 2000).…”
Section: Model Estimationsupporting
confidence: 85%
See 2 more Smart Citations
“…Cycles do not feature in any markets over the observed sample period. This is consistent with most of the tourism demand literature using CSMs, such as the studies of González and Moral (1995) and Kulendran and Witt (2003). It indicates that the key economic determinants included have successfully explained the variation in the tourism demand variable, and therefore it is not necessary to include an additional cyclical component (Moosa, 2000).…”
Section: Model Estimationsupporting
confidence: 85%
“…Both the BSM and the CSM have been applied in the tourism demand forecasting context, and several studies have demonstrated their superior forecasting performance relative to other time series alternatives (see for example González & Moral, 1995, 1996Kulendran & King, 1997;Kulendran & Witt, 2001;Turner & Witt, 2001). However, in the studies of both Turner and Witt (2001) and Kulendran and Witt (2003), the CSM produced less accurate forecasts than the BSM.…”
Section: Modelling and Forecasting Seasonal Tourism Demandmentioning
confidence: 87%
See 1 more Smart Citation
“…The consumer price indices were used as a proxy for the cost of tourism in Malaysia relative to the cost of living in Australia adjusted by the exchange rate [19][20][21] . We therefore expect a negative sign for this variable.…”
Section: Tourism Pricementioning
confidence: 99%
“…In this study, Naïve method was used. SES model (Chen et al, 2008;Witt et al, 1994), SMA model (Makridakis et al, 1998;Hu et al, 2004;Lim and McAleer, 2008), Box-Jenkins model (Makridakis and Hibon, 1979), ARIMA (Kim et al, 2011;Goh and Law, 2002;Preez and Witt, 2003), Holt's DES model (Lim and McAleer, 2001;Makridakis et al, 1998), BSM model (Greenidge, 2001;Gonzalez and Moral, 1995;Turner and Witt, 2001;Kulendran and Witt, 2003) are other time series methods used by scholars. Casual econometric methods are other quantitative forecasting methods.…”
Section: Introductionmentioning
confidence: 99%